2014
DOI: 10.1159/000363658
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Combined Low- and Standard-Dose Trospium and Solifenacin for Moderate Overactive Bladder Symptoms in Elderly Men and Women

Abstract: Objective: To increase the safety and effectiveness of treatments for overactive bladder (OAB) with moderate symptoms in elderly patients. Patients and Methods: Patients were examined at the Urodynamic Department of the Regional Diagnostic Center (Vladivostok, Russian Federation) from September 1, 2012 to December 31, 2012. The assignment of patients [n = 177, average age 69. 4 years, 98 women (55.4%) and 79 men (44.6%)] was random and blind in this placebo-controlled study. Patients were distributed into subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 19 publications
(18 reference statements)
0
33
0
Order By: Relevance
“…Four articles were identified that examined the use of anticholinergic medications in combination with each other (Table ) . Three of the four studies were conducted by Kosilov et al at the Institute of Physical Health in Russia.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles were identified that examined the use of anticholinergic medications in combination with each other (Table ) . Three of the four studies were conducted by Kosilov et al at the Institute of Physical Health in Russia.…”
Section: Resultsmentioning
confidence: 99%
“…Following a review of the abstracts, 491 citations were rejected for not meeting study inclusion criteria (ie, wrong study type, not OAB; no elderly patients, not β‐3 adrenergic agonists or muscarinic antagonists), 381 were excluded following full‐text review, and 18 were excluded during the data extraction phase for not meeting study inclusion criteria—17 of these included elderly patients but were post‐hoc analyses of elderly sub‐groups; one paper reported the open‐label extension phase of a trial. A total of eight RCT papers met all the study inclusion criteria and were included in the review …”
Section: Resultsmentioning
confidence: 99%
“…Combined antimuscarinic agents were used in some of our patients. It has been reported that combined antimuscarinic agents could provide good clinical and urodynamic effects for elderly, refractory, neurogenic or even child OAB patients . However, while a β3‐adrenoceptor agonist is available, a combination of antimuscarinics and mirabegron may be a good alternative for refractory OAB patients to avoid additive adverse effects of combined antimuscarinic agents …”
Section: Discussionmentioning
confidence: 99%